Differentiation of Campylobacter fetus Subspecies by Proteotyping - Emele, Matthias F. (Eur J Microbiol Immunol (Bp), 2019)
Campylobacter fetus is a causative agent of intestinal illness and, occasionally, severe systemic infections and meningitis. C. fetus currently comprises three subspecies: C. fetus subspecies fetus (Cff), C. fetus subspecies venerealis (Cfv), and C. fetus subspecies testudinum (Cft). Cff and Cfv are primarily associated with mammals whereas Cft is associated with reptiles. To offer an alternative to laborious sequence-based techniques such as multilocus sequence typing (MLST) and polymerase chain reaction (PCR)-ribotyping for this species, the purpose of the study was to develop a typing scheme based on proteotyping. In total, 41 representative C. fetus strains were analyzed by intact cell mass spectrometry and compared to MLST results. Biomarkers detected in the mass spectrum of C. fetus subsp. fetus reference strain LMG 6442 (NCTC 10842) as well as corresponding isoforms were associated with the respective amino acid sequences and added to the C. fetus proteotyping scheme. In combination, the 9 identified biomarkers allow the differentiation of Cft subspecies strains from Cff and Cfv subspecies strains. Biomarkers to distinguish between Cff and Cfv were not found. The results of the study show the potential of proteotyping to differentiate different subspecies, but also the limitations of the method.